The Modulatory Effects of Intermittent Theta Burst Stimulation in Combination With Mirror Hand Motor Training on Functional Connectivity: A Proof-of-Concept Study - Zhang, Jack Jiaqi; Fong, Kenneth N. K. (Frontiers in Neural Circuits, 2021)
Mirror training (MT) is an observation-based motor learning strategy. Intermittent theta burst stimulation (iTBS) is an accelerated form of excitatory repetitive transcranial magnetic stimulation that has been used to enhance the cortical excitability of the motor cortices. This study aims to investigate the combined effects of iTBS with MT on the resting state functional connectivity at alpha frequency band in healthy adults. Eighteen healthy adults were randomized into one of three groups – Group 1: iTBS plus MT, Group 2: iTBS plus sham MT, and Group 3: sham iTBS plus MT. Participants in Groups 1 and 3 observed the mirror illusion of the moving (right) hand in a plain mirror for four consecutive sessions, one session/day, while participants in Group 2 received the same training with a covered mirror. Real or sham iTBS was applied daily over right motor cortex prior to the training. Resting state electroencephalography at baseline and post-training was recorded when participants closed their eyes. The mixed-effects model demonstrated a significant interaction effect in the coherence between FC4 and C4 channels, favoring participants in Group 1 over Group 3 (Δβ = -0.84, p = 0.048). A similar effect was also found in the coherence between FC3 and FC4 channels favoring Group 1 over Group 3 (Δβ = -0.43, p = 0.049). In contrast to sham iTBS combined with MT, iTBS combined with MT may strengthen the functional connectivity between bilateral premotor cortices and ipsilaterally within the motor cortex of the stimulated hemisphere. In contrast to sham MT, real MT, when combined with iTBS, might diminish the connectivity among the contralateral parietal-frontal areas.